Three methods for inoculation of viral vectors into plants - Monroy-Borrego, Andrea G.; Steinmetz, Nicole F. (Frontiers in Plant Science, 2022)
Agriculture is facing new challenges, with global warming modifying the survival chances for crops, and new pests on the horizon. To keep up with these challenges, gene delivery provides tools to increase crop yields. On the other hand, gene delivery also opens the door for molecular farming of pharmaceuticals in plants. However, towards increased food production and scalable molecular farming, there remain technical difficulties and regulatory hurdles to overcome. The industry-standard is transformation of plants via Agrobacterium tumefaciens, but this method is limited to certain plants, requires set up of plant growth facilities and fermentation of bacteria, and introduces lipopolysaccharides contaminants into the system. Therefore, alternate methods are needed. Mechanical inoculation and spray methods have already been discussed in the literature – and here, we compare these methods with a newly introduced petiole injection technique. Because our interest lies in the development of plant viruses as immunotherapies targeting human health as well as gene delivery vectors for agriculture applications, we turned toward tobacco mosaic virus as a model system. We studied the effectiveness of three inoculation techniques: mechanical inoculation, Silwet-77 foliar spray and petiole injections. The foliar spray method was optimized, and we used 0.03% Silwet L-77 to induce infection using either TMV or a lysine-added mutant TMV-Lys. We developed a method using a needle-laden syringe to target and inject the plant virus directly into the vasculature of the plant – we tested injection into the stem and petiole. Stem inoculation resulted in toxicity, but the petiole injection technique was established as a viable strategy. TMV and TMV-Lys were purified from single plants and pooled leaf samples – overall there was little variation between the techniques, as measured by TMV or TMV-Lys yields, highlighting the feasibility of the syringe injection technique to produce virus nanoparticles. There was variation between yields from preparation to preparation with mechanical, spray and syringe inoculation yielding 40–141 mg, 36–56 mg, 18–56 mg TMV per 100 grams of leaves. Similar yields were obtained using TMV-Lys, with 24–38 mg, 17–28, 7–36 mg TMV-Lys per 100 grams of leaves for mechanical, spray and syringe inoculation, respectively. Each method has its advantages: spray inoculation is highly scalable and therefore may find application for farming, the syringe inoculation could provide a clean, aseptic, and controlled approach for molecular farming of pharmaceuticals under good manufacturing protocols (GMP) and would even be applicable for gene delivery to plants in space.